E-learning Implementation Assistance is Fun for Paud Teachers in Argasunya Village, Cirebon City - Amalia Zubaedah, Putri (Devotion : Journal of Research and Community Service, 2021)
The impact of the Covid-19 pandemic is felt by all levels of society and all aspects of life, including early childhood education. Educational units must have the readiness of human resources in the form of educators and education staff as well as the readiness of technology facilities so that the learning process can be carried out effectively and efficiently. However, not all PAUD units are able to carry out internet-based learning which is called e-learning. This study aims to provide assistance in implementing a fun E-Learning for PAUD teachers in Argasunya Village, Cirebon City. This study uses a qualitative method. The community service steps taken are through webinars, question and answer and discussion. The results of this study can be concluded that the understanding of participants in implementing e-learning increases through examples of fun activities that parents can do at home so that they can stimulate all aspects of child development